Evaluation of Learning Management Standards to Improve Higher Education Quality Standards Through Internal Quality Audits - Komalasari, Yeti; Anton Abdullah; Wildan Nugraha; Eska Nugraha, Minulya; Zusnita Hermala; Saripa; M. Wahid Alqorni (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Independent evaluation is required through an internal quality control system through internal quality audit activities. This study evaluated the achievement of learning management standards, inhibiting factors, and recommendations for improving education quality standards at Palembang Polytechnic. This type of qualitative research uses observation methods, structured interviews, and literature studies. The research instrument is the author directly involved in the research. The informants in this study were determined using a purposive technique: three research informants. The study’s results obtained data on implementing internal quality audits on learning management standards that have not been implemented. An effective internal quality management model is needed as a platform or application that supports collecting, storing, and managing data and information on website-based internal quality management system services to support fast, precise, and efficient internal quality management system integration.